Characterization of Rhizoctonia solani associated with soybean in Brazil - Fenille, Roseli Chela [UNESP]; De Souza, Nilton Luiz [UNESP]; Kuramae, Eiko Eurya [UNESP] (Springer Nature, 2002)
Rhizoctonia solani causes pre- and post-emergence damping-off, root and hypocotyl rot and foliar blight in soybean. Foliar blight has resulted in yield losses of 31-60% in north and northeast Brazil. The aim of this study was to characterize isolates of R. solani associated with soybean in Brazil. Among 73 Rhizoctonia isolates examined, six were binucleate and 67 were multinucleate. The multinucleate isolates were characterized according to hyphal anastomosis reaction, mycelial growth rate, thiamine requirement, sclerotia production, and RAPD molecular markers. Four isolates that caused hypocotyl rot belonged to AG-4 and using RAPD analysis they grouped together with the HGI subgroup. Another isolate that caused root and hypocotyl rots was thiamine auxotrophic, grew at 35 °C, and belonged to AG-2-2 IIIB. All 62 isolates that caused foliar blight belonged to AG-1 IA. RAPD analysis of R. solani AG-1 IA soybean isolates showed high genetic similarity to a tester strain of AG-1 IA, confirming their classification. The teleomorph of R. solani, Thanatephorus cucumeris was produced in vitro by one AG-1 IA isolate from soybean. The AG-4 and AG-2-2 IIIB isolates caused damping-off and root and hypocotyl rots of soybean seedlings cv. 'FT-Cristalina', under greenhouse conditions. The AG-2-2 IIIB isolate caused large lesions on the cortex tissue, that was distinct from the symptoms caused by AG-4 isolates. The AG-1 IA isolates caused foliar blight in adult soybean plants cv. 'Xingu' under the greenhouse and also in a detached-leaf assay.
Keywords: Anastomosis groups; RAPD analysis; Thanatephorus cucumeris; thiamine; fungal disease; soybean; anastomosis; Brazil; cultivar; damping off disease; fungal plant disease; fungus growth; fungus isolate; plant yield loss; root rot; teleomorph; Rhizoctonia solani